Optimization of the process of solid radwaste management at the ”Shelter” object transformation to the ecologically safety system - Batiy, V.G.; Stojanov, A.I. (Вопросы атомной науки и техники, 2007)
Methodological approach of optimization of schemes of solid radwaste management of the ”Shelter” object and ChNPP industrial site during transformation to the ecologically safe system was developed.